Tamoxifen-Dependent Induction of AGR2 Is Associated with Increased Aggressiveness of Endometrial Cancer Cells - Hrstka, Roman; Podhorec, Jan; Nenutil, Rudolf; Sommerova, Lucia; Obacz, Joanna; Durech, Michal; Faktor, Jakub; Bouchal, Pavel; Skoupilova, Hana; Vojtesek, Borivoj (Cancer investigation, 2017)
Tamoxifen treatment in breast cancer patients is associated with increased risk of endometrial malignancies. Significantly, higher AGR2 expression was found in endometrial cancers that developed in women previously treated with tamoxifen compared to those who had not been exposed to tamoxifen. An association of elevated AGR2 level with myometrial invasion occurrence and invasion depth was also found. In vitro analyses identified a stimulatory effect of AGR2 on cellular proliferation. Although adverse tamoxifen effects on endometrial cells remain elusive, our work identifies elevated AGR2 as a candidate tamoxifen-dependent mechanism of action responsible for increased incidence of endometrial cancer.
Keywords: nádory endometria; proliferace buněk; Female; Mucoproteins; Endometrial cancer; tamoxifen; invazivní růst nádoru; ženské pohlaví; Up-Regulation; onkogenní proteiny; MFC-7 buňky; transfekce; Transfection; endometrium; lidé; MCF-7 Cells; upregulace; Oncogene Proteins; A549 Cells; signální transdukce; hormonální protinádorové látky; mukoproteiny; Proteins; Signal Transduction; AGR2; pohyb buněk; Cell Transformation, Neoplastic; Risk Factors; retrospektivní studie; proteiny; Adenocarcinoma; adenokarcinom; Cell Proliferation; rizikové faktory; Endometrium; RNA Interference; nádorová transformace buněk; Endometrial Neoplasms; Tamoxifen; Cell Movement; Antineoplastic Agents, Hormonal; RNA interference; Neoplasm Invasiveness; Breast cancer; Retrospective Studies; buňky A549; Humans